Florence Nightingale - Shor, Donnali; Renna, Gianni ([Morristown, N.J.] : Silver Burdett Co., 1986)
Recounts the life story of the English girl who became a famous nurse and dedicated herself to the alleviation of suffering at home and abroad.
Includes index.
Bibliography: p. 61.
5.6
5-8.
Keywords: Nightingale, Florence, -- 1820-1910 -- Juvenile literature; Nightingale, Florence, -- 1820-1910.; Nightingale, Florence, -- 1820-1910.; Nurses -- England -- Biography -- Juvenile literature; Nurses; Nurses